Aprovechamiento de residuos biomásicos del limón (Citrus limon), en la obtención de aceites esenciales, para la elaboración de productos agroindustriales en la provincia Bolívar - Aucatoma Tandapilco, Daniel Isaías (2023)
The objective of the research was to take advantage of the biomass residues of the lemon (Citrus limon), to obtain essential oils, for the production of agroindustrial products in the province of Bolivar. A bibliographic review was made about the raw material (peel), the methods of extraction of the essential oil through simple and fractional distillation, maceration as a method of softening the peel, gas chromatography analysis for the determination of the main compounds of the essential oil and the mathematical models that can be applied for the modeling of extraction kinetics and yield of the distillation process. The raw material came from the areas of Echeandía, Caluma, Las Naves belonging to the Bolivar province. The experimentation was carried out in the Extracts Laboratory of the Agroindustrial Complex of the Agroindustry Career. An AxBxC (4x2x2), factorial arrangement design was applied with three replications, where the study factors were: lemon variety with (4 levels), maceration with (2 levels), extraction method with (2 levels). The simple and fractional distillation method was used, applying a maceration process of 8 and 12 hours to the lemon peel, the time used for distillation was 120 minutes. The study variables were volume, yield, density and pH. A volume of 2,300 mL was obtained and a yield of 0,970% belonging to the Sutil lemon variety (T2), the density was 0,850 g/mL corresponding to (T4) and pH was 4,64 in the Mandarino lemon variety (T11). Seven main compounds were determined, the major component was limonene with 60,35% in the Subtle lemon, 72,84% in the Mandarin lemon, 82,50% in the Royal lemon and 81,75% in the Tahiti lemon, which shows that the essential oil is of good quality. The experimental results were adjusted to 4 mathematical models for extraction kinetics and for yield; since the model that best adjusted to the extraction kinetics was the Multiplicative model with R2 = 0,998%; for the yield modeling the Gompertz model was adjusted with an R2 = 0,992%. A bar soap was produced using the best treatment of the essential oil according to density (T4). In conclusion, it is indicated that lemon (Citrus limon), biomass residues contribute an abundant raw material for obtaining different quality agroindustrial products, such as the extraction of lemon essential oil, presented in this research.